Oncological outcomes of cryosurgery as primary treatment in T3 prostate cancer: experience of a single centre. (21st January 2015) - Guo, Zhi; Si, Tongguo; Yang, Xueling; Xu, Yan
<x xml:space="preserve">Abstract</x> Objective To assess the oncological outcomes and determine prognostic factors for overall survival (OS), cancer‐specific survival (CSS), and biochemical progression‐free survival (BPFS) after cryosurgery for clinical stage T3 prostate cancer. Patients and Methods Between 2002 and 2007, 75 patients with clinical stage T3 prostate cancer received cryosurgery as primary treatment in our institution. No adjuvant treatment was provided until biochemical failure. After biochemical failure, hormone therapy was administered. Kaplan–Meier analysis was used to calculate the OS, CSS, and BPFS. Cox regression was used to identify factors predictive of survival. Results Clinical stage T3a (cT3a) was detected in 60% (45/75) of patients and cT3b detected in 40% (30/75). The 5‐year OS, CSS, and BPFS rates were 85.3%, 92.0%, and 48%, respectively. There was a significant difference when comparing the pT3a with the pT3b group for 5‐year OS (88.9% vs 80%, P = 0.02) and BPFS (55.6% vs 36.7%, P = 0.01), but there was no difference in CSS (93.3% vs 90%, P = 0.63). Stage, Gleason score, and nadir prostate‐specific antigen (PSA) were associated with BPFS, while Gleason score and nadir PSA were the most significant predictors for CSS. Conclusions Cryosurgery can offer good 5‐year OS, CSS, and BPFS rates for cT3 prostate cancer, and there was no difference between T3a and T3b for CSS. Gleason score and nadir PSA were the most significant predictors of survival. Further clinical trials are warranted for evaluating the role of cryosurgery for cT3 prostate cancer.